The perfluoroalkyl substance (PFAS) contamination level in milk and milk products in Poland. (September 2019) - Sznajder-Katarzyńska, Katarzyna; Surma, Magdalena; Wiczkowski, Wiesław; Cieślik, Ewa
Abstract: Cross-sectional studies concerning the contamination of milk and milk products by perfluoroalkyl substances (PFASs) are presented and the extent of contamination that may occur in food samples, collected in Poland in 2016 is evaluated; not only milk, cottage cheese, natural yoghurt and butter but also previously untested foods, including kefir, sour cream and Camembert-type cheese. Levels of 7 perfluoroalkyl carboxylic acids (PFCAs) and 3 perfluoroalkane sulfonates (PFSAs) were analysed using the QuEChERS extraction method followed by micro-HPLC-MS/MS. All PFASs were detected with an RSD of lower than 10%. The most commonly detected was perfluorooctanoic acid, followed by perfluorobutanoic acid and perfluorohexane sulfonate, on par with perfluorooctane sulfonate. The largest contributor to the total PFAS concentration in the investigated food samples was perfluorobutanoic acid, and its summary concentration within the group was estimated to be 13.34 ng g −1 . The results for 43.4% of samples analysed were greater than LOQ (limit of quantification).